Assembly of porous lanthanide metal–organic frameworks constructed by chalcone dicarboxylic acid and exploration of their properties. (1st September 2019) - Pan, Wei; Gong, Chunhua; Zeng, Xianghua; Hu, Chenyan; Zhang, Yi; Zhu, Dun-Ru; Xu, Hao; Guo, Haiyang; Zhang, Junyong; Xie, Jingli
Graphical abstract: 3D lanthanide metal–organic frameworks (Ln–MOFs) with honeycomb cavities shown photocatalytic activities for the degradation of organic dyes. Abstract: Using rational designed chalcone dicarboxylic acid ligand (H2 L ), a series of lanthanide metal–organic frameworks (Ln–MOFs) with the general formulaLn(HL)3 (Ln  = La ;Ce ;Pr ;Nd ;Sm ;Eu ;Gd ) have been obtained under the solvothermal reaction. The crystal structure analysis displays that all theLn –MOFs are the isomorphic three-dimensional (3D) metal–organic frameworks with honeycomb cavities, in which the porosity is ∼20% that calculated via PLATON software. In addition, photocatalytic activities of Ln–MOFs for the degradation of several organic dyes have been explored, suggesting that Ln–MOFs can be used as efficient heterogeneous photocatalyst for the degradation of organic dyes.